2021
DOI: 10.1038/s41598-021-82937-3
|View full text |Cite
|
Sign up to set email alerts
|

Palladin isoforms 3 and 4 regulate cancer-associated fibroblast pro-tumor functions in pancreatic ductal adenocarcinoma

Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) has a five-year survival under 10%. Treatment is compromised due to a fibrotic-like stromal remodeling process, known as desmoplasia, which limits therapeutic perfusion, supports tumor progression, and establishes an immunosuppressive microenvironment. These processes are driven by cancer-associated fibroblasts (CAFs), functionally activated through transforming growth factor beta1 (TGFβ1). CAFs produce a topographically aligned extracellular matrix (ECM) that correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…Importantly, we aim to report that eribulin also acts directly on CAFs and prompts these cells to generate an ECM that no longer effectively promotes PDAC cell invasive spread and has lost its ability to nurture PDAC cells under nutritional stress. Of note, the observed CAF-generated ECM functional shift, from tumor-supportive to tumor-suppressive, simulated reported results that were obtained with TGFβ deficient CAFs in our CDM system [15, 22, 33]. Hence, this study proposes that eribulin could be used as a stroma-normalizing agent.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Importantly, we aim to report that eribulin also acts directly on CAFs and prompts these cells to generate an ECM that no longer effectively promotes PDAC cell invasive spread and has lost its ability to nurture PDAC cells under nutritional stress. Of note, the observed CAF-generated ECM functional shift, from tumor-supportive to tumor-suppressive, simulated reported results that were obtained with TGFβ deficient CAFs in our CDM system [15, 22, 33]. Hence, this study proposes that eribulin could be used as a stroma-normalizing agent.…”
Section: Introductionsupporting
confidence: 81%
“…To this end, β5 KO CAFs constitute an ideal human cellular model as these cells present with a phenotype and function akin to perpetuating TGFβ inhibition [15]. In fact, β5 KO CAFs have been reported to generate CDMs with tumor-suppressive functions and traits [15, 22, 33]. Using β5 KO CAFs, we previously demonstrated that canonical TGFβ signaling is necessary for the production of tumor-supportive ECMs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations